Verbal And Narrative Strategies of Resistance: Countering Western Orientalist Othering in Persepolis (Volume 1) - Wulan Prihatiningsih Sholikhah; Ruly Indra Darmawan (Universitas Islam Negeri Palopo, 2026)
This study examines how Persepolis challenges Western stereotypes about Iran, which are often portrayed as uniform and oppressive. Rather than focusing only on representation, this study analyzes how meaning is constructed through narrative and verbal strategies. Drawing on Gerald Prince’s narratology (1982), it focuses on point of view, temporal distance, direct discourse, summary narration, and symbolic expression. Using a qualitative textual approach, the analysis is based on a close reading of selected excerpts. The findings show that meaning is not presented as fixed or complete, but constructed through perspective and experience. An internal point of view limits knowledge and foregrounds a partial understanding, while temporal distance enables reinterpretation. Direct discourse introduces multiple, conflicting voices, while summary narration condenses events without full explanation. Symbolic expressions reveal how ideology operates through simple language. Together, these strategies produce a layered, open, and interpretive narrative that resists reducing Iranian society to a single, fixed image.